BRAND IDENTITY BIRO TRAVEL PADANG TOUR WISATA PULAU - Muhammad Rio Akbar; Agung Eko Budi Waspada (Institut Seni Indonesia Padang Panjang, 2016)
ABSTRACT In West Sumatra, there is the potential of maritime tourism because of its many islands created into tourism destination. Those islands are Pemutusan Island, Panggang Island, Emas Island (Swarnadwipa beach and resort) and other islands. The existence of those islands results on the appearance of travel bureaus related to maritime tourism; and one of them is the travel bureau of Padang Tour Wisata Pulau. The travel bureau of Padang Tour Wisata Pulau designed its brand identity in order to support its promotion hence it became effective and efficient. The writer used logo as the primary media and website, social media, leaflet, poster, banner, t-shirt, key chain, tote bag, CD/CD cover, life vest, name card, sticker, ticket, and stamp as the supplementary media for promotional benefit. Those media function as interactive information that is visible by the lovers of maritime tourism. This designing aims at facilitating the fans of maritime tourism who want to visit maritime tourisms in West Sumatera.